Dynamics of debris flow-induced impacting onto rigid barrier with material source erosion-entrainment process - Li, Bailong; Fang, Youliang; Li, Yanying; Zhu, Chun (Frontiers in Earth Science, 2023)
The dynamics of debris flow impact considering the material source erosion-entrainment process is analyzed using a coupled SPH–DEM-FEM method. A complex coupled dynamic model of a debris flow, the erodible material source, and a rigid barrier is established in this paper. The applicability of the coupled SPH–DEM-FEM method for calculating the impact force of debris flow on the rigid barrier is verified by comparing the m o d e l with the laboratory test. The strain softening model is used to simulate the process from solid state to transition state and finally to liquid state of erodible material source. The impact force caused by debris flow considering the source erosion-entrainment process and the dynamic response of a rigid barrier is also analyzed. The results show that the volume of debris fluid, impact force, and dynamic response of a rigid barrier considering source erosion–entrainment are significantly greater than those of the original model. According to the calculation results, the existing formula for the impact force of a debris flow is then modified. The coupled numerical analysis method and the calculated results help to clarify the influence of erosion-entrainment, modify the calculation of the impact force of debris flow, and optimize the design of the rigid barrier.